2004
DOI: 10.1089/152308604322899404
|View full text |Cite
|
Sign up to set email alerts
|

Role of Adenosine Receptor Activation in Antioxidant Enzyme Regulation During Ischemia–Reperfusion in the Isolated Rat Heart

Abstract: The aim of the present study was to investigate the protective role of pharmacological preconditioning on antioxidant enzymes using A(1) and A(3) adenosine receptor agonists in the recovery of the isolated myocardium after cardioplegic ischemia. Two different modes of preconditioning were studied: isolated rat hearts were perfused with A(1) receptor agonist 2-chloro-N(6)-cyclopentyladenosine (CCPA) or A(3) 2-chloro-N(6)-(3-iodobenzyl) adenosine-5'-N-methyluronamide (Cl-IB-MECA) (1 nM), followed by cardioplegic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 37 publications
(39 reference statements)
0
9
0
Order By: Relevance
“…Also, the SODmimetic EUK-8 was cardioprotective in isolated hearts from adult OVX female rats (47). Perhaps of greatest interest is the report of increased SOD activity following pharmacological preconditioning with the adenosine A 1 receptor agonist CCPA in isolated rat hearts (15), since PKCε is known to be activated downstream of the A 1 receptor (11). It is likely that increases in GPX and SOD2 immediately following PKCε activation may serve to combat increased reactive oxygen species production in the aged female heart (29).…”
Section: Discussionmentioning
confidence: 99%
“…Also, the SODmimetic EUK-8 was cardioprotective in isolated hearts from adult OVX female rats (47). Perhaps of greatest interest is the report of increased SOD activity following pharmacological preconditioning with the adenosine A 1 receptor agonist CCPA in isolated rat hearts (15), since PKCε is known to be activated downstream of the A 1 receptor (11). It is likely that increases in GPX and SOD2 immediately following PKCε activation may serve to combat increased reactive oxygen species production in the aged female heart (29).…”
Section: Discussionmentioning
confidence: 99%
“…33 Our group previously reported on the protective role of pharmacological preconditioning with A1 and A3 adenosine receptor agonists in I/R-induced injury in the isolated rat heart. 34 The use of selective adenosine A2A receptor agonists for pharmacologic hepatic preconditioning in humans is supported by the successful application of adenosine for myocardial protection during coronary angioplasty. 35 Recently, Yadav et al, 36 using the TUNEL assay and measurements of intrahepatic caspase-3 activity, found that ischemic preconditioning in mouse liver confers dramatic protection against prolonged ischemia by inhibiting apoptosis through downregulation of caspase-3 activity.…”
Section: Discussionmentioning
confidence: 99%
“…A fluid-filled latex balloon was inserted via the left atrium into the left ventricle and inflated to set a left-ventricular end-diastolic pressure (LVEDP) between 5–10 mmHg. Coronary flow was collected every 10 min, left ventricular developed pressure (LVP) was continuously recorded and the derivatives ±dP/dt max were calculated by the CODAS data acquisition system (San Diego, CA, USA) [13]. Hearts were excluded from further data analysis as a result of one of the following undesirable situations: 1.…”
Section: Methodsmentioning
confidence: 99%
“…Activation of this receptor preconditions cardiomyocytes in culture, in isolated hearts, and in vivo protects against the damaging effects of ischemia/reperfusion injury. A 3 AR agonists are attractive as cardioprotective agents because they do not alter systemic hemodynamic parameters in non-rodent species and are effective upon preischemic administration or only during reperfusion [813]. The prototypical A 3 AR agonists N 6 -(3-iodobenzyl)-adenosine-5′- N -methylcarboxamide (IB-MECA) and its 2-chloro derivative Cl-IB-MECA have been tested in experimental animal models of ischemia/reperfusion injury [14,15].…”
Section: Introductionmentioning
confidence: 99%